TELEDERMATOLOGY MUTIRON AT POLICLINICA BARRAL Y BARRAL IN RIO BRANCO – ACRE IN 2023 - Renne Silva de Castro, Carlos; dos Santos da Silva Castro, Miracelia; José Angel, Douglas (Health and Society, 2025)
Dermatological diseases are one of the main causes of people seeking care in Primary Health Care (PHC), often being treated by non-specialized doctors, which leads to an increase in unnecessary referrals to dermatologists and an overload on specialized services. This scenario is, in part, caused by the limited academic training of professionals, affecting their ability to diagnose and treat dermatological conditions appropriately. Teledermatology appears as a promising solution to optimize care, using information and communication technologies to facilitate remote diagnosis, allowing PHC doctors to receive reports from dermatologists within 72 hours, without the need for unnecessary travel. Objective: To report the experience of the Teledermatology joint effort held at Policlínica Barral Y Barral in the municipality of Rio Branco in the State of Acre, aimed at reducing waiting times and improving access to dermatological care. Method: This is a literature review study in the form of a professional experience report with critical analysis. The data was collected from medical and administrative records that provided the necessary information to carry out the experience and its results. Results: During the joint effort, 200 PHC patients were expected, with 142 treated, 128 exams validated and 50 cases treated directly in PHC, avoiding unnecessary referrals. The results showed a predominance of injuries classified as green (secondary) and blue (primary care) risk, with some serious cases, such as skin cancer, being referred to specialized care. Conclusion: Teledermatology proved to be effective in speeding up diagnosis and treatment, improving the resolution of PHC and optimizing public resources. The experience highlighted the importance of training PHC professionals to diagnose and treat dermatological diseases, highlighting the need to integrate telemedicine into health practices, contributing to more efficient and accessible care.